Multi-Data Integration Towards a Global Understanding of the Neurological Impact of Human Brain Severe Acute Respiratory Syndrome Coronavirus 2 Infection - Mesmoudi, Salma; Lapina, Colline; Rodic, Mathieu; Peschanski, Denis (Frontiers in Integrative Neuroscience, 2022)
As the COVID-19 pandemic continues to unfold, numerous neurological symptoms emerge. The literature reports more and more manifestations of SARS-CoV-2 related to headache, dizziness, impaired consciousness, cognitive impairment, and motor disorders. Moreover, the infection of SARS-CoV-2 may have a durable neurological impact. ACE2/TMPRSS2 are the main entry point into cells for some strains of coronaviruses including SARS-CoV-2, which uses it to target the central nervous system. The aim of this study is to characterise the scope of the potential complex impact of a SARS-CoV-2 infection in the brain. It concerns different scales: the topographic, cognitive, sensorimotor, and genetic one. We investigated which cognitive and sensorimotor functions are associated with the brain regions where ACE2/TMPRSS2 are overexpressed, hypothesizing that they might be particularly affected by the infection. Furthermore, overexpressed genes in these regions are likely to be impacted by COVID-19. This general understanding is crucial to establish the potential neurological manifestations of the infection. Data on mRNA expression levels of genes were provided by the Allen Institute for Brain Science, and the localisation of brain functions by the LinkRbrain platform. The latter was also used to analyse the spatial overlap between ACE2/TMPRSS2 overexpression, and either function-specific brain activations, or regional overexpression of other genes. The characterisation of these over-expressed genes was based on the GeneCards platform and the gene GSE152075 from the Gene Expression Omnibus database. We analysed the cognitive and sensorimotor functions whose role might be impaired, of which 88 have been categorized into seven groups: memory and recollection, motor function, pain, lucidity, emotion, sensory and reward. Furthermore, we categorized the genes showing a significant increase in concentration of their mRNAs in the same regions where ACE2/TMPRSS2 mRNA levels are the highest. 11 groups emerged from a bibliographical research: neurodegenerative disease, immunity, inflammation, olfactory receptor, cancer/apoptosis, executive function, senses, ischemia, motor function, myelination, and dependence. The results of this exploration could be in relation with the neurological symptoms of COVID-19. Furthermore, some genes from peripheral blood are already considered as biomarker of COVID-19. This method could generate new hypotheses to explore the neurological manifestations of COVID-19.